Tumor thickness and depth of invasion in squamous cell carcinoma of tongue as indicators of the loco-regional spread of the disease: A preliminary study - Rupsa Das; Satya Ranjan Misra; Satya Sundar Gajendra Mohapatra; Pravakar Bahinipati; Smita Rani Priyadarshini; Alkananda Sahoo; Debahuti Mishra; Anamika Rai (Elsevier, 2024)
Background: Magnetic resonance imaging (MRI) is a routinely used imaging modality for pre-treatment radiologic evaluation of tongue carcinoma, providing accurate information regarding the extent of the disease. Aims and objectives: To investigate the role of MRI-derived depth of invasion and tumor thickness evaluation in squamous cell carcinoma of the tongue, and to assess if any correlation exists between depth of invasion, tumor thickness, nodal metastasis, muscles, and space involved. Materials and methods: Thirty-three patients with oral squamous cell carcinoma of the tongue who had undergone pre-treatment MRI and excisional biopsy were included. The tumor thickness (TT) and depth of invasion (DOI) were evaluated on MRI and histopathologic images. Result: The relation between different methodologies for assessing showed a very high correlation for the tumor tissue thickness (r = 0.99, p < 0.05) and depth of invasion (r = 0.82, p < 0.05). The tumor thickness and the depth of invasion increased with the loss of differentiation in the carcinoma histopathologically. As the depth of invasion increases, the extent of the spread of the carcinoma to tongue musculature, lingual septum, and spaces also increases. Conclusion: The present study has depicted a high correlation between the tumor thickness and the depth of invasion between MRI and histopathological findings and is the first of its kind to correlate DOI to the invasiveness of the disease.